A Desirable Perception and Behavior of Thai Courtesy of Chinese Students in Chiang Mai University - Ma, Xiaomin; Maneeku, Jarunee; Mangkhang, Charin (Journal of Graduate MCU KhonKaen Campus, 2019)
The purpose of this research were. To study the habits and manners of Thailand recognized and to study the problems of learning and education approach to learning the etiquette of Thailand in Chiang Mai University students. The sample used is the Chinese students studying in the Faculty of Humanities, University of Chiang Mai. The total number of 57 people by selecting a specific method. Tools used in this research is the questionnaire and interview etiquette and style of Thailand in Chiang Mai University students. Statistics used in the analysis include percentage frequency values, average, standard deviation and use statistical tests of correlation Pearson (Pearson Product Moment Correlation) research found that 1) students of Thailand is a desirable etiquette by images included on many levels. Average is equal to 3.54 and Thai etiquette desirable behavior of Chinese students in the overall picture was at a moderate level With an average of 3.43 2) learning problems stories Thailand manners, the most common is to respect 3) students have problem-solving approach to learning the etiquette of Thailand desirable in respect by learning through the media. Video of tv and movies.